Strategies to improve male involvement in PMTCT Option B+ in four African countries: a qualitative rapid appraisal - Donela Besada; Sarah Rohde; Ameena Goga; Nika Raphaely; Emmanuelle Daviaud; Vundli Ramokolo; Vuyolwethu Magasana; Nobuntu Noveve; Tanya Doherty (Taylor & Francis Group, 2016)
Background: The World Health Organization recommends that antiretroviral therapy be started as soon as possible, irrespective of stage of HIV infection. This 'test and treat' approach highlights the need to ensure that men are involved in prevention of mother-to-child HIV transmission (PMTCT). This article presents findings from a rapid appraisal of strategies to increase male partner involvement in PMTCT services in Uganda, Democratic Republic of Congo, Malawi, and Côte d'Ivoire in the context of scale-up of Option B+ protocol. Design: Data were collected through qualitative rapid appraisal using focus groups and individual interviews during field visits to the four countries. Interviews were conducted in the capital city with Ministry of Health staff and implementing partners (IPs) and at district level with district management teams, facility-based health workers and community health cadres in each country. Results: Common strategies were adopted across the countries to effect social change and engender greater participation of men in maternal, child and women's health, and PMTCT services. Community-based strategies included engagement of community leaders through dialogue and social mobilization, involving community health workers and the creation and strengthening of male peer cadres. Facility-based strategies included provision of incentives such as shorter waiting time, facilitating access for men by altering clinic hours, and creation of family support groups. Conclusions: The approaches implemented at both community and facility levels were tailored to the local context, taking into account cultural norms and geographic regional variations. Although intentions behind such strategies aim to have positive impacts on families, unintended negative consequences do occur, and these need to be addressed and strategies adapted.A consistent definition of 'male involvement' in PMTCT services and a framework of indicators would be helpful to capture the impact of strategies on cultural and behavioral shifts. National policies around male involvement would be beneficial to streamline approaches across IPs and ensure wide-scale implementation, to achieve significant improvements in family health outcomes.